2007
DOI: 10.4049/jimmunol.179.11.7791
|View full text |Cite
|
Sign up to set email alerts
|

An IL-17F/A Heterodimer Protein Is Produced by Mouse Th17 Cells and Induces Airway Neutrophil Recruitment

Abstract: IL-17A and IL-17F are related homodimeric proteins of the IL-17 family produced by Th17 cells. In this study, we show that mouse Th17 cells also produce an IL-17F/A heterodimeric protein. Whereas naive CD4+ T cells differentiating toward the Th17 cell lineage expressed IL-17F/A in higher amounts than IL-17A/A homodimer and in lower amounts than IL-17F/F homodimer, differentiated Th17 cells expressed IL-17F/A in higher amounts than either homodimer. In vitro, IL-17F/A was more potent than IL-17F/F and less pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
252
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(264 citation statements)
references
References 41 publications
(50 reference statements)
10
252
1
1
Order By: Relevance
“…Moreover, these γδ-T cells were producing IL-17 ( Fig. 2G), causing damage rather than tolerance as suggested previously (7,(17)(18)(19)(20).…”
Section: Resultssupporting
confidence: 74%
“…Moreover, these γδ-T cells were producing IL-17 ( Fig. 2G), causing damage rather than tolerance as suggested previously (7,(17)(18)(19)(20).…”
Section: Resultssupporting
confidence: 74%
“…IL-17F is a proinflammatory cytokine with functions initially reported as similar to those of IL-17A and sharing the same receptor (45). Recent studies have revealed that IL-17A and IL-17F can be expressed as homo-or heterodimers that may bind IL-17 receptors with various affinities and may play not completely redundant functions (26,46,47). We found expression of IL-17F in only a fraction of IL-17A-secreting cells from NTreg, indicating the existence of distinct subpopulations that differentially express these cytokines and may be functionally distinct, an observation that warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…There is a mutual interplay between neutrophils and CD4 + T helper 17 cells (Th17) [62]. While IL-17 and CXCL8 secreted by Th17 cells induce the recruitment of neutrophils, secretion of CCL2 and CCL20 by activated neutrophils attracts Th17 cells [61][62][63]. Th17 cells may further modulate neutrophil activity through secretion of TNFα, IFNγ and GM-CSF [62].…”
Section: Niche-dependent Neutrophil Functionmentioning
confidence: 99%